Competitiveness model based on Pythagorean Fuzzy Topsis approach to establish the labor indicator in a future scenario of the Industry 4.0 - Borunda Agular, María Inés; Perez Olguin, Ivan Juan Carlos; Martinez Gomez, Erwin Adan (Asociación Mexicana de Logística & Cadena de Suministro, 2021)
This research presents an innovative model associated with the human factor and its future change in Industry 4.0, considering a model of future competitiveness associated with a set of Pythagorean Fuzzy Topsis to determine the real impact of the effects of the Generation Z envelope on the use of this type of technology. Considering the radical evolution in the way working methods are conceived, the collaborative team structure based on technical knowledge, capable of creating and sustaining technological infrastructures. A Pythagorean Model is implemented to adequately model the competitiveness of a company associated with Industry 4.0 under a Blockchain Model. This paper applies a decision method under the paradigm of the Multicriteria Decision Making (MCDM) Theory under the perspective of fuzzy logic, to carry out the decision making in simulated environments. The fundamental contribution lies in the adaptation of this theory for this type of environment.